Age- and Gender-Associated Staphylococcus aureus spa Types Found among Nasal Carriers in a General Population: the Tromsø Staph and Skin Study. - Sangvik, Maria; Olsen, Renate Slind; Olsen, Karina; Simonsen, Gunnar Skov; Furberg, Anne-Sofie; Sollid, johanna u ericson (Journal of Clinical Microbiology, 2011)
The published version of this paper is part of Maria Sangvik's doctoral thesis, which is available in Munin at http://hdl.handle.net/10037/4738 Staphylococcus aureus nasal carriers risk autoinfection; however, knowledge about the factors that make specific strains successful colonizers is limited. This study was undertaken to identify the most successful S. aureus clones in nasal carriers and compare their distribution among host groups. The population structure of S. aureus isolates from healthy adults was investigated by spa typing 1,981 isolates from persistent and intermittent nasal carriers participating in a health survey. In the baseline screening (1,113 isolates), the most common spa types were t012 (8.4%), t084 (7.6%), and t065 (4.9%). Three large spa clonal complexes (spa CC012, spa CC065, and spa CC084) comprised 62.4% of the isolates. In multivariate models adjusted for age and smoking status, male sex was associated with higher risk for spa type t084 (odds ratio [OR], 1.72; 95% confidence interval [CI], 1.06 to 2.77), and lower risk of spa type t012 (OR, 0.60; 95% CI, 0.39 to 0.92) colonization. The prevalence of spa type t012 decreased significantly with increasing age (P = 0.03), with a prevalence almost twice as high in the youngest group (age 30 to 44 years, prevalence = 11.1%) as in the oldest group (age, 60 to 87 years; prevalence = 5.6%). Among baseline isolates, spa type t084 had a twofold-higher prevalence among intermittent carriers than among persistent carriers (10.6% versus 5.5%; P = 0.04). In summary, the two most prevalent spa types found in this study were significantly associated with age and/or gender. This may provide valuable clues to the multifactorial mechanisms, among them bacterial factors, involved in nasal colonization with S. aureus.